Frank Wilkinson Speaks at Fresno American Civil Liberties Union Meeting - Watkins, Howard::::::::: (1983)
??, Hague Foster, ?, Jacqueline Pillar, Lorri Foster, ?; Back: Cindy Calvert, Frank Wilkinson, Geneva Bennett, Scott Williams, Sam Gitchel